Parental Investment and the Intergenerational Transmission of Economic Preferences and Attitudes - Maria Zumbühl; Thomas Dohmen; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2013)
We study empirically whether there is scope for parents to shape the economic preferences and attitudes of their children through purposeful investments. We exploit information on the risk and trust attitudes of parents and their children, as well as rich information about parental efforts in the upbringing of their children from the German Socio-Economic Panel Study. Our results show that parents who invest more in the upbringing of their children are more similar to them with respect to risk and trust attitudes and thus transmit their own attitudes more strongly. The results are robust to including variables on the relationship between children and parents, family size, and the parents' socioeconomic background.
Keywords: D1; D8; J13; J62; Z13; 330; risk preferences; trust; intergenerational transmission; cultural transmission; social mobility; GSOEP; Eltern; Risikopräferenz; Vertrauen; Kognition; Kinder; Soziale Mobilität; Generationengerechtigkeit; Deutschland